2020
DOI: 10.1016/j.dib.2020.106246
|View full text |Cite
|
Sign up to set email alerts
|

MRI data confirm the selective involvement of thalamic and amygdalar nuclei in amyotrophic lateral sclerosis and primary lateral sclerosis

Abstract: A standardised imaging protocol was implemented to evaluate disease burden in specific thalamic and amygdalar nuclei in 133 carefully phenotyped and genotyped motor neuron disease patients. “Switchboard malfunction in motor neuron diseases: selective pathology of thalamic nuclei in amyotrophic lateral sclerosis and primary lateral sclerosis” [1] “Amygdala pathology in amyotrophic lateral sclerosis and primary lateral sclerosis” [2] Raw volumetric data, group compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…Patients with ALS exhibited GM volume reduction in the motor cortex and the thalamus as shown in a longitudinal study ( 8 ). In a recent large cohort MRI-based study, Chipika and colleagues have shown atrophy of thalamic nuclei in both the chromosome 9 open reading frame 72 (C9orf72) carrier and noncarrier patients with ALS, demonstrating thalamus as a potential pathological area in the brain ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Patients with ALS exhibited GM volume reduction in the motor cortex and the thalamus as shown in a longitudinal study ( 8 ). In a recent large cohort MRI-based study, Chipika and colleagues have shown atrophy of thalamic nuclei in both the chromosome 9 open reading frame 72 (C9orf72) carrier and noncarrier patients with ALS, demonstrating thalamus as a potential pathological area in the brain ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Reduced volumes were noted in the amygdala in ALS patients without C9orf72; however, in ALS patients carrying the GGGGCC hexanucleotide repeats in C9orf72 , abnormalities in thalamic and amygdala nuclei were observed. These data demonstrate genotype-specific patterns in ALS [ 27 ].…”
Section: Classificationmentioning
confidence: 74%
“…This phenotype displays a relatively long survival [ 26 ]. It has been recently published that both ALS and PLS patients exhibited focal thalamus atrophy showing extrapyramidal motor degeneration [ 27 ]. Reduced volumes were noted in the amygdala in ALS patients without C9orf72; however, in ALS patients carrying the GGGGCC hexanucleotide repeats in C9orf72 , abnormalities in thalamic and amygdala nuclei were observed.…”
Section: Classificationmentioning
confidence: 99%
“…These findings support the recent PLS consensus classification system and argues for earlier intervention/inclusion into clinical trials [ 55 , 57 , 58 , 59 ]. Another volumetric study comparing 100 patients with ALS with 33 PLS patients and 100 controls found significant volumetric differences between subgroups with PLS, demonstrating unique volumetric losses in the thalamic sensory nuclei and lateral geniculate region and sparing of the amygdala as compared to ALS patients [ 60 ]. In addition to hyperintensity of the CST, HSP may demonstrate several unique findings identified on conventional MRI such as thinning of the corpus callosum in SPG11 or diverse findings such as leukodystrophy, hypomyelination, spinal cord or cerebellar atrophy, or hydrocephalus in complex forms of HSP [ 39 , 41 ].…”
Section: Diagnosticsmentioning
confidence: 99%